Towards more specific O6-Methylguanine-DNA methyltransferase (MGMT) inactivators - CORDEIRO MACHADO, ALESSANDRA; MC MURRY, THOMAS; ROZAS, ISABEL (My University, 2011)
Searching for a novel family of inactivators of the human DNA repair protein O6?methylguanine?DNA methyltransferase (MGMT) which is known to bind to the DNA minor groove, we have computationally modelled and synthesised two series of 2?amino?6?aryloxy?5?nitropyrimidines with morpholino or aminodiaryl substituents (potential minor groove binders) at the 4?position. Synthesis of these compounds was achieved by successive substitution of each of the two Cl atoms of 2?amino?4,6?dichloro?5?nitropyrimidine by the corresponding amino and aryloxy derivatives. Biochemical evaluation of these compounds as MGMT inactivators showed poor activities, but in general the 4?bromothenyloxy derivatives showed better inactivation than the benzyloxy versions. DNA binding assessment was not possible due to insolubility problems.
PUBLISHED
Keywords: Genetics; DNA Repair